2023
DOI: 10.1590/1413-812320232810.10072023
|View full text |Cite
|
Sign up to set email alerts
|

Condições de trabalho e biossegurança dos profissionais de saúde e trabalhadores invisíveis da saúde no contexto da COVID-19 no Brasil

Maria Helena Machado,
Maria Carlota de Rezende Coelho,
Everson Justino Pereira
et al.

Abstract: Resumo O artigo versa sobre as condições de trabalho na saúde no contexto da pandemia no Brasil. Trata-se de estudo transversal que utilizou dados de recorte das pesquisas “Condições de trabalho dos profissionais de saúde no contexto da Covid-19 no Brasil” e “Os Trabalhadores invisíveis da saúde: condições de trabalho e saúde mental no contexto da Covid-19 no Brasil”, objetivando conhecer as condições de trabalho e a biossegurança desses dois contingentes profissionais distintos e desiguais, socialmente. A aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…This is an article of a descriptive nature based on legal references in order to support the analysis of the data from the studies "Work conditions of healthcare workers in the context of Covid-19 in Brazil" 2 (matrix project) and "Invisible healthcare workers: work conditions and mental health in the context of Covid-19 in Brazil" 3 . These are cross-sectional studies, with nationwide reach, which counted on the participation of 15,132 health professionals (HP) and 21,480 "invisible" health professionals, (IHP) who are at the technical, assistant, and support levels of healthcare, respectively, who were working during the pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an article of a descriptive nature based on legal references in order to support the analysis of the data from the studies "Work conditions of healthcare workers in the context of Covid-19 in Brazil" 2 (matrix project) and "Invisible healthcare workers: work conditions and mental health in the context of Covid-19 in Brazil" 3 . These are cross-sectional studies, with nationwide reach, which counted on the participation of 15,132 health professionals (HP) and 21,480 "invisible" health professionals, (IHP) who are at the technical, assistant, and support levels of healthcare, respectively, who were working during the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, precarious legal relationships, excessive WS, low salaries, moral harassment. and low resilience constitute the sad reality of the HP in Brazil, as the studies have revealed 2,3 .…”
Section: Expansion Of the Workload In Healthmentioning
confidence: 99%
“…Em 2020, pesquisa com os profissionais de saúde pública no Brasil mostrou que apenas 69,5% e 64,1% dos profissionais de enfermagem e médicos, respectivamente, afirmavam ter recebido equipamento de proteção individual (EPI) de forma contínua durante a pandemia, enquanto somente 34,1% dos agentes comunitários em saúde e agentes de combate a endemia afirmaram o mesmo. A disponibilidade e o treinamento para o uso adequado dos EPIs estavam presentes para cerca de 65,0% dos trabalhadores invisíveis da saúde (TIS) 36,37 (Quadro 1).…”
Section: Cenário Nacionalunclassified
“…Para desenvolver e realizar este cuidar da vida, necessitamos de um imensa e complexa força de trabalho em saúde (FTS) com configuração, volume de ocupações, grande diversidade de qualificações específicas e que demandam capacitações permanentes e regulamentação profissional específica. Segundo Machado a saúde vive em um estágio de pré-cidadania profissional 36,37 .…”
Section: Repercussões Nas Condições De Trabalho Dos Trabalhadores Da ...unclassified
See 1 more Smart Citation